Interwencjonizm w agrobiznesie na przykładzie PROW 2007–2013– teoria i praktyka - Wigier, Marek; Chmurzyńska, Katarzyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Interventionism is a form of government’s active influence on the economy in order to achieve given goals. RDP 2007–2013 is an example of the intervention policy, interacting through its instruments on the agribusiness sector. The article presents the theoretical assumptions of interventionism and attempts to assess of the state intervention and the most tangible effects of the program